Improving the functional and instantaneous properties of pre-gelatinized riceberry powder through pulsed fluidized-bed agglomeration - Duangkhamchan, Wasan; Siriamornpun, Sirithon (Italian Journal of Food Science, 2025)
This study investigated the enhancement of the functional properties of pre-gelatinized riceberry powder (PRP) through pulsed fluidized-bed agglomeration using inulin as a binder. Response surface methodology was employed to optimize binder concentration (10–20%) and feed rate (3.5–5.5 mL·min⁻¹) based on key parameters, including final moisture content (6.89–9.46% wb), process yield (71.4–87.2%), and mean particle size (D50, 367–464 μm). The optimal conditions of 20% binder concentration and a 5.5 mL·min⁻¹ feed rate resulted in an acceptable moisture content (≤10% wb), a high process yield of 87.2%, and a D50 of 464 μm. Agglomeration significantly improved water holding capacity (7.83 g·g⁻¹), oil holding capacity (7.35 g·g⁻¹), and bulk properties such as bulk density, tapped density, particle density, and porosity. These enhancements were attributed to the porous granule structure formed during agglomeration and the amphiphilic nature of inulin, which facilitates hydrophilic and hydrophobic interactions. The combination of inulin and agglomeration also showed potential to moderate the glycemic response while expanding the applicability of PRP in plant-based foods for health-conscious consumers. Despite the powder's high cohesiveness (Carr index 32.5%, Hausner ratio 1.34), it exhibited improved wettability, dispersibility, and reconstitution properties. These findings highlight pulsed fluidized-bed agglomeration with inulin as a promising approach for developing high-performance, plant-based powders for food and beverage applications.